Advanced squamous cell carcinoma of the temporal skin – case report - Bilewicz, Robert; Doroszyńska-Tomczyk, Magdalena; Dalke, Krzysztof; Świątkiewicz, Andrzej; Zieliński, Andrzej (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction: Skin cancer is the most common human malignant neoplasm. It is mainly found on uncovered parts of the skin exposed to the sun. The treatment of choice is surgery. Objective: The aim of the study is to present a case of advanced carcinoma of the scalp and to discuss treatment strategies. Case report: The 88-year-old man with extensive relapsing temporal skin cancer was treated with surgery. His main complaint was headaches. The tumour was removed with selective cervical neck dissection and reconstruction procedures simultaneously. The wound was covered by dislocation of a skin flap from the parietal area. Histopathological examination revealed basal cell carcinoma. Metastases to regional lymph nodes were not found. After 5 months’ observation a local relapse appeared. The needle aspiration biopsy showed squamous cell carcinoma. Then palliative treatment was introduced. Conclusions: Extensive resection of a malignant tumour of the head and neck in some cases is possible and more beneficial in spite of poor prognosis. Discrepancies in histopathological examination in these cases do not affect the planning of treatment strategy. In therapy of extensive loss of skin of the head and neck regional flaps can be used. Then interdisciplinary treatment is required.